The Consequences of Excessive Vegetable Production (American Journal of Multidisciplinary Research and Innovation, 2022)
Using a survey-interview method on 50 randomly selected farmers, the study intends to report the effects of excessive vegetable production in a barangay on farmers’ economic conditions, traditional practices, interactions, and the environment. The respondents were composed of 52% middle-aged farmers, 28% young farmers, and 20% elderly farmers; 76% were male and 24% were female. Economically, vegetable cultivation has increased farmers’ financial capability, provided a source of income for others, made others reliant on the supply system, and caused others to accumulate debt. Traditional farming methods were abandoned. Furthermore, excessive vegetable farming caused soil loosening, pesticide waste disposal issues, biodiversity loss owing to agricultural expansion, conversion of rice fields to vegetable farms that lead to the endangerment of other species, and the emergence of non-beneficial organisms. In addition, the Amuyo system was enhanced, non-involvement in social functions, and farmer conflicts were linked to excessive vegetable production activities. It is recommended that a study concerning the conditions of soils in all the farms in the barangay should be conducted; a study on the elimination of the insect that causes the rotting of vegetable fruits and fruit trees; carrying out training on sustainable agricultural practices and environmental issues; formation of a farmers’ organization and farmers’ cooperatives; establishment of a conservation area for indigenous species; creation of vegetable product development facility; and undertake a similar study with a larger research area and respondents.